DogCatcher allows loop-friendly protein-protein ligation - Keeble, A; Yadav, V; Matteo, F; Bauer, C; Chuntharpursat-Bon, E; Bon, R; Huang, J; Howarth, MR (Cell Press, 2021)
There are many efficient ways to connect proteins at termini. However, connecting at a loop is difficult because of lower flexibility and variable environment. Here we have developed DogCatcher, a protein that forms a spontaneous isopeptide bond with DogTag peptide. DogTag/DogCatcher was generated initially by splitting a Streptococcus pneumoniae adhesin. We optimized DogTag/DogCatcher through rational design and evolution, increasing reaction rate 250-fold and establishing millimolar solubility of DogCatcher. When fused to a protein terminus, DogTag/DogCatcher reacts slower than SpyTag003/SpyCatcher003. However, inserted in loops of a fluorescent protein or enzyme, DogTag reacts much faster than SpyTag003. Like many membrane proteins, the ion channel TRPC5 has no surface-exposed termini. DogTag in a TRPC5 extracellular loop allowed normal calcium flux and specific covalent labeling on cells in 1 minute. DogTag/DogCatcher reacts under diverse conditions, at nanomolar concentrations, and to 98% conversion. Loop-friendly ligation should expand the toolbox for creating protein architectures.